The Influence of Work Environment and Communication on Employee Work Motivation at Legian Beach Hotel Kuta, Indonesia - Ida Bagus Putra Manuaba; I Made Gede Darma Susila; Desak Made Purnama Dewi (Tourism and Hospitality Insights, 2025)
Introduction: Human resources are a key factor in the success of the hospitality industry. One essential aspect that influences performance is employee work enthusiasm. This study investigates how the work environment and communication affect employee work enthusiasm, both individually and simultaneously, at Legian Beach Hotel Kuta. Methods: This research used a quantitative approach with a descriptive-correlational design. The population consisted of 76 employees from the Food and Beverage Department. A saturated sampling technique was applied, involving the entire population as the sample. Data were collected through structured questionnaires and analyzed using descriptive statistics and multiple linear regression with SPSS version 24.0. Results: The analysis showed that the work environment (X1) had a positive and significant partial effect on work enthusiasm. Communication (X2) also had a positive and significant partial effect. Simultaneously, the work environment and communication had a significant and positive influence on employee work enthusiasm. Conclusion: The findings indicate that both the work environment and communication are critical factors in enhancing employee enthusiasm. Hotel management is advised to improve these aspects to support employee motivation and performance. Future research is recommended to explore other potential variables that may influence work enthusiasm beyond those examined in this study.